Analisis Kepuasan Pelanggan Restoran Makanan Crispy di Indonesia: Studi Kasus di Dr. Chicken Cimahpar - Aqila Asysyakur (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
This study aims to evaluate the level of customer satisfaction at Dr. Chicken Cimahpar, a crispy or fresh food restaurant in Indonesia. The problem at hand is how to determine the level of customer satisfaction based on the attributes of the product or service they receive. The method used is the Customer Satisfaction Index (CSI), which determines the level of user satisfaction based on the level of performance and the level of importance of the measured product or service features. The sample of this research is consumers who visit and purchase products in the second observation stage and are willing to be respondents for research. The results showed that Dr. Chicken Cimahpar has a customer satisfaction level of 78.59%, which is within the